Pixações embucetadas: mensagens visuais da cultura popular como ato de resistência na paisagem alternativa de Aracaju com base no marxismo - Silva, Fernando Marinho Fernandes da (2022)
This dissertation studies pixação made by women in Aracaju between 2019 and 2021. The research is based on the following guiding question: Do pixações bucetalada, buceta, buceta..., Juno, coragem and xibiuti constitute visual messages of acts of resistance? Thus, the objective of this work is to understand the pixações of feminist aspects in Aracaju as visual messages of acts of resistance. We understand that it is important to investigate such visual manifestations that point to feminist issues such as the debate about the autonomy of the female body, freedom and occupation of public spaces, sorority and the strengthening of the feminine condition. Another issue that justifies this investigation is that pixação is perceived as a markedly masculine activity, and identifying pixações produced by women as an important phenomenon interrupts the reproduction of a process of invisibilization of women. And, also, for the possibility of approaching a marginalized and criminalized popular culture, highlighting its contradictions and disputes. The study is based on: the concept of Act of Resistance as Popular Culture in Marilena Chaui (2021a), the Feminist Marxism approach in Taylisi Leite (2020), and the Excluded Alternative Landscape in Denis Cosgrove (1998). In the approach to studying pixações in addition to the fundamental concepts, we used Dondis' (1997) notion of Levels of Visual Message and Frutiger's (1999) Diversity of Sign Appearance to relate to the visual aspects of the six pixações. Thus, the approach was effectively qualitative, as it aims to better understand human behavior and experience. The research was developed in five stages: photographic mapping, theoretical foundation, definition of the research corpus, semi-structured interviews with pixadoras, and a study of the pixações. We take pixações as a metaphor for the tattooed skin of the city, for both the city expresses the social contradictions in its landscape, and the feminine body, in a broad sense, does the same. We understand pixação from a strongly political point of view and emphasize the notion that culture as work and resistance is given by the struggle against the dominant ideology. From this notion, we understand pixações as an act of resistance and, consequently, of popular culture. We observed a potential for criticism of capitalist patriarchy in the pixações studied, based on Roswitha Schulz's theorem of value-clivage and feminist Marxism, which is characterized by radical and revolutionary adherence to generate a new model of society. We found that pixações, in the context of the city, define an excluded alternative landscape, as they are characterized by a rich symbology disregarded by the dominant classes. As main visual aspects of pixações we identify here the use of the feminine symbol, the use of words that highlight the female body, the grouping of women's pixações, the drawings with radical simplification, the handwritten letters with curves that extend, the influence of the stick letter, and the hastily made handwritten letters. In summary, as a production of meaning derived from our studies of the visual messages, we understand that in these pixações the symbolized female body is free, is identified, is in movement, is beautiful, is joyful, and is collective. We understand the pixações studied here to be embucetadas in the sense that they use signs of their own bodies, get angry, and protest against the patriarchal capitalist system that silences, immobilizes, and oppresses them. Therefore, they are configured as acts of resistance to this entire order of oppressions.